Genetic variations in TAOK1, TMTC4, NTF3, and CNTN1 and their association with noise-induced hearing loss - G. Oztan; H. Issever; F. Oguz; M. Atak; E. Ezirmik; Y. Guldiken (Kuwait Journal of Science)
Noise-induced hearing loss (NIHL) affects more than 10% of the adult population in developed countries, especially those with high noise levels. This study's objective is to examine the effect of the variability in sensitivity to noise exposure of genetic variations in the TAOK1, TMTC4, NTF3, and CNTN1 genes. A total of 323 people in seven different businesses were included in the scope of the research. SNP genotyping was performed over a total of eight SNP regions, including SNP regions from the TAOK1, TMTC4, NTF3, and CNTN1 genes, using the ABI 7500 Real-Time PCR System with 96 wells according to the rs191010498 TAOK1 C/T, rs1469121309 TAOK1 A/T, rs763560019 TMTC4 T/A, rs1484543954 TMTC4 G/C, rs1334049414 NTF3 T/C, rs1438314793 NTF3 G/A, rs762307549 CNTN1 G/A,T, and rs745850349 CNTN1 T/A Custom TaqMan® SNP Genotyping Assays and standard protocols. The CT heterozygous frequencies of the TAOK1 gene were observed, and age, working time, and working in a noisy environment over 85 dBA (p ​< ​0.05) were found to be significantly higher in the hearing loss group compared to those in the control group. In the Turkish population, sensitivity to noise-induced hearing loss was observed in five out of eight SNP regions of the TAOK1, TMTC4, NTF3, and CNTN1 genes, with TAOK1, TMTC4, and CNTN1 genes also being associated with hearing loss. However, no statistically significant difference was found in the NTF3 genes regarding rare variants. The results show the TAOK1-rs191010498 (p ​= ​0.01), TAOK1-rs1469121309 (p ​= ​0.03), TMTC4-rs763560019 (p ​= ​0.01), CNTN1-rs762307549 (p ​= ​0.01), and CNTN1-rs745850349 (p ​= ​0.03) polymorphisms to be associated with NIHL. Identifying TAOK1, TMTC4, CNTN1 polymorphisms is important in terms of providing a new contribution to the genetic roles associated with hearing loss.